Flurry of the Snombies : The Notebook of Doom #7 - Cummings, Troy (New York, NY : Scholastic Inc., 2015)
It is a very hot summer in Stermont, and Alexander and his friends are at Camp Gloamy in the mountains, but even here there are monsters--specifically zombie snowmen called snombies who want to freeze the young monster-hunters.
Keywords: Monsters -- Juvenile fiction; Snowmen -- Juvenile fiction; Camps -- Juvenile fiction; Friendship -- Juvenile fiction; Monsters -- Fiction; Snowmen -- Fiction; Camps -- Fiction; Friendship -- Fiction; Horror stories; Horror fiction; Horror fiction